2022
DOI: 10.1007/s12079-022-00687-x
|View full text |Cite
|
Sign up to set email alerts
|

METTL13 facilitates cell growth and metastasis in gastric cancer via an eEF1A/HN1L positive feedback circuit

Abstract: Although improved treatment could inhibit progression of gastric cancer (GC), the recurrence and metastasis remain challenging issues. Methyltransferase like 13 (METTL13) has been implicated in most human cancers, but its function and mechanism in GC remain elusive. In the present study, we evaluated its expression in GC samples and found it was aberrantly overexpressed in cancer tissues than that in normal stomach tissues. High expression of METTL13 was closely associated with age, tumor size and T classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…Previously, METTL13 expression was markedly raised, and an absence of METTL13 greatly inhibited proliferation at the same time as it potentiated apoptosis in vitro, and hindered tumor growth in vivo in head and neck squamous cell carcinoma 8 . In addition, METTL13 overexpression drove cell growth and migration in gastric cancer 10 . Consistently, we also noted an abnormal upregulation of METTL13 in NPC cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previously, METTL13 expression was markedly raised, and an absence of METTL13 greatly inhibited proliferation at the same time as it potentiated apoptosis in vitro, and hindered tumor growth in vivo in head and neck squamous cell carcinoma 8 . In addition, METTL13 overexpression drove cell growth and migration in gastric cancer 10 . Consistently, we also noted an abnormal upregulation of METTL13 in NPC cells.…”
Section: Discussionsupporting
confidence: 84%
“…8 In addition, METTL13 overexpression drove cell growth and migration in gastric cancer. 10 Consistently, we also noted an abnormal upregulation of METTL13 in NPC cells. METTL13 knockdown not only disturbed NPC cell proliferation, migration and invasion along with angiogenesis, but also retarded tumor growth.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study underscores the critical role of cell elongation and morphological changes in the migration, growth, and metastasis of cancer cells, as highlighted in previous research [22,23]. Speci cally, ADSCs have been reported to facilitate the EMT in various cancers, including lung and pancreatic cancers [24,25].…”
Section: Verifying Interaction With Breast Cancer Cells and Adscs Thr...supporting
confidence: 68%
“…An intriguing aspect of this research is the observed interaction between EEF1A2 and HSPB8, where EEF1A2 serves to positively regulate the expression of HSPB8 [ 47 ]. A pivotal role for EEF1A2 emerged in a recent study in gastric cancer revealed that METTL13, which is linked to cancers in humans, works together with EEF1A2 in a loop that causes abnormal levels of the cancer-promoting gene HN1L [ 48 ]. Interestingly, the results from the TCGA dataset (STAD) for stomach adenocarcinoma showed a significant decrease in EEF1A2 expression compared with adjacent normal tissue and GTEx normal samples (Fig.…”
Section: Eef1a2 Switching On In Tumorigenesismentioning
confidence: 99%